TI_GERICHTE 12.2012.86 vom 31. Januar 2014 , Lavoro - divieto di concorrenza - provvedimento cautelare - diritto alla prova - TI Tribunale d'appello (2014)
Lavoro - divieto di concorrenza - provvedimento cautelare - diritto alla prova